Bacillus sp. GLN Laccase Characterization: Industry and Biotechnology Implications - Asemahle Gogotya; Nonso E. Nnolim; Uchechukwu U. Nwodo (Applied Sciences)
Laccases are multicopper oxidases that exhibit a broad substrate spectrum, making them excellent biocatalysts for clean technological processes. The study isolated novel laccase-producing bacteria from decomposed wood samples and characterized the enzyme for potential industrial and biotechnological applications. The results showed that three bacteria, SP-2, SP-1, and WP-2, out of the eight isolated bacteria, oxidized both guaiacol and α-naphthol in the plate assay and exhibited extracellular laccase activity of 7.0 ± 0.01, 6.67 ± 0.02, and 7.40 ± 0.04 (U/mL), respectively. WP-2 was selected for further study and was identified as Bacillus sp. GLN (accessioned number: MK290989). Strain GLN maximally secreted laccase 48 h post-fermentation, with an enzyme yield of 36.83 ± 2.47 U/mL in optimized conditions. The crude laccase was optimally active at pH 9.0 and 90 °C and showed excellent pH and thermal stability, retaining approximately 65% residual activity at 100 °C for 270 min. GLN laccase demonstrated remarkable stability after treatment with organic solvents and metal ions, retaining more than 50% of its original activity in the presence of 100 mM inhibitors. The data from this study highlight the relevance of Bacillus sp. GLN and its laccase in promoting clean technology.